PENERAPAN SUPERVISI PENDIDIKAN DI LINGKUNGAN LEMBAGA NON-FORMAL - Rizqi Maulana Ilmi; Galuh Prabowo; Muh. Khotibul Umam (JIP: Jurnal Ilmu Pendidikan, 2024)
This research aims to explore the challenges and strategies involved in implementing educational supervision in non-formal institutions, as well as exploring how this affects the quality of education in that context. Through a thorough literature search and analysis of relevant case studies, this research identifies several main issues that arise in the practice of educational supervision in non-formal institutions. Among these are difficulties in establishing effective communication, the diversity of educational programs offered, and the diverse needs of non-formal educators. The research methodology approach includes in-depth analysis of existing literature and case research to gain a comprehensive understanding of the challenges faced. The findings highlight the need for flexible and inclusive supervision approaches, as well as the importance of collaboration between supervisors and non-formal educators to improve the overall quality of education. The implications of this research emphasize the need to develop guidelines and best practices in educational supervision in non-formal institutions in order to increase learning effectiveness and better optimize student potential.